Aksi Restorasi Penanaman Mangrove Dalam Memitigasi Bencana - Bambang Gunawan; Nurlina; Sri Purwanti; Sri Hidayati; Yeni Ika Pratiwi; Mahrus Ali; Fauziatun Nisak (Universitas Merdeka Surabaya, 2022)
The restoration of mangrove planting in the coastal area of ​​Gunung Anyar Village was carried out as a mitigation measure. The mangroves here function as a barrier when high tide occurs. With the mangroves, the tidal waves that occur can be muffled by the mangroves so that the impact of damage that occurs on land can be minimized. This is reinforced by the existence of government regulations with the aim of minimizing disaster damage, namely Law no. 24 of 2007 concerning Disaster Management. The action of planting mangrove plants in one area of ​​Surabaya City, especially the Gunung Anyar sub-district, Rungkut District is a series of community service activities for lecturers and students at Merdeka University Surabaya in 2022. This area has the potential for beaches to be used as new land for the development of mangrove plants because it is a coastal area that Of course, it is very vulnerable to seawater abrasion. The purpose of this service activity is to mitigate disasters, especially the risk of seawater abrasion, flash floods as well as to increase the potential of local areas in developing mangrove tourism, as well as improving brackish water ecosystems, especially fisheries development.